Statio publici portorii in Novae (Niedermoesien) und eine neue Statuenbasis aus dem Stabsgebäude der 1. Italischen Legion - Sarnowski , Tadeusz (Studia Europaea Gnesnensia, 2017)
The present paper is a publication of a new portorium inscription found in one of the late Roman loess pits in the courtyard of the principia (headquarters building) of the legio I Italica and testifying to the existence of the station of the great Illyrian customs district at Novae. The stone bears a dedication to Numen Augusti and Genius portorii and was set up by two servi vilici from the station staff on behalf of G. Iulius Eutyches, the conductor of the Illyrian customs district. The author of the paper dates the stone to AD 169-175 and tries to localise the station near the eastern gate of the legionary fortress. The critical context of the publication includes the findspot of the inscription, topography of the area situated directly to the east of the fortress, location of the Roman landing place and finally also the scene XXXV of the Trajan’s column representing a fortress on the Danube bank which can be identified with Novae.